Theoretic and Methodological Aspects of Consideration of Lawfulness - Мінченко, Ольга Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article depicts genesis of doctrinal construction of the category of lawfulness‖ and peculiarities ofapproaches to its definition. The role of lawfulness in the mechanism of legal regulation is shown.